Detection of Salmonella in chicken meat and chicken using conventional and rapid culture methods. - Azizan, Syamsyul; Abdul Aziz, Saleha (2011)
A study on the detection of Salmonella in chicken meats and chickens using conventional and rapid culture methods was conducted over a four weeks period in Selangor area of Malaysia. Thirty chicken meats of various parts included wing, breast and thigh were sampled from three markets and 75 cloacal swabs were sampled from three farms located near UPM. Two isolation methods used in this study were conventional culture method and rapid culture method for both food and cloacal swab samples. Of the thirty chicken meats sampled, three (10%) were positive for Salmonella. The occurrence of Salmonella in chicken meat maybe due to contamination during handling, processing, supply, transportation and the processing areas. Of the 75 cloacal swabs sampled, four (5.3%) were positive for Salmonella. The occurrence of Salmonella in chicken may due to poor management and stress. From the two isolation methods used, rapid culture method isolated 10% of Salmonella in chicken meat and none from cloacal swabs. On the other hand, the conventional method isolated 5.3% of Salmonella from cloacal swabs and none from chicken meat. The presence of Salmonella in chickens and chicken meat is of public health importance.